ELEVATING TEACHER EMPOWERMENT THROUGH INDONESIA’S TEACHER PROFESSIONAL EDUCATION PROGRAM - Darmuh, Muthia Mutmainnah; Utami R, Winda Ayu; Kadar, Annisa Syauqina (THE ACADEMIC: ENGLISH LANGUAGE LEARNING JOURNAL, 2025)
This study explores the transformative effects of Indonesia’s Teacher Professional Education Program (TPEP) on educators, focusing on its impact on teachers’ personal and professional growth. Using a qualitative phenomenological approach, data were gathered through interviews, focus group discussions, and classroom observations involving program participants (teachers) and faculty members. Key findings reveal significant positive changes: teachers reported adopting more innovative teaching methods (e.g. project-based and technology-enhanced learning), improved classroom management, and increased confidence and job satisfaction. For example, one participant noted that after TPEP 'students are more engaged and disciplined when I use project-based learning and new digital tools.' These practical changes align with prior research showing that active, student-centered professional development enhances instructional practice. However, participants also cited persistent challenges: resource constraints, heavy workloads, and limited ongoing PD support hindered full implementation. Stakeholders emphasized the need for strengthened support mechanisms (such as richer resource libraries and mentoring), echoing other studies that highlight institutional backing as critical for PD success. Overall, TPEP has empowered teachers and raised instructional quality, but sustainable improvements will require addressing systemic barriers and investing in continuous, collaborative professional learning